2013
DOI: 10.1038/labinvest.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

The restorative effects of adipose-derived mesenchymal stem cells on damaged ovarian function

Abstract: The clinical application of human adipose-derived mesenchymal stem cells (MSCs) as treatment for intractable diseases or traumatic tissue damage has attracted attention. To address the ability of reactivating injured ovaries, we prepared a rat model with damaged ovaries by using an anticancer agent, cyclophosphamide (CTX). We then investigated the restorative effects on ovarian function and the safety of adipose-derived MSCs (A-MSCs). MSCs were shown to be capable of inducing angiogenesis and restoring the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 42 publications
(38 reference statements)
10
110
1
2
Order By: Relevance
“…A very recent report showed that ADSCs were capable of restoring the ovarian follicles and corpus lutea after induced damage of ovaries with cyclophosphamide [29]. Consistent with our immunohistochemical findings, we found that ADSCs also were as effective as estrogen in promoting endometrial proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…A very recent report showed that ADSCs were capable of restoring the ovarian follicles and corpus lutea after induced damage of ovaries with cyclophosphamide [29]. Consistent with our immunohistochemical findings, we found that ADSCs also were as effective as estrogen in promoting endometrial proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence has shown that hUCMSCs have unique advantages compared to BMSCs (22), which make them a promising source of cells for treatment. According to previous studies, stem cells to treat ovarian injury are primarily administered via intravenous injection (IV) or in situ ovarian micro injection (MI) (23)(24)(25)(26). However, very few studies have examined suitable forms of hUCMSC therapy to delay ovarian aging.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown in animal models that MSCs from different sources (e.g. adipose) can improve or even restore ovarian function [56][57][58][59]. To determine the ideal age at which POMSCs could be used to regenerate ovaries, the ovarian tissue of more patients at different ages would need to be included.…”
Section: Discussionmentioning
confidence: 99%